Enhancing Inter-Ethnic Harmony in a Multicultural Society: Lessons from a Case Study of the Harmonization of Malay and Chinese Ethnicities in Belitung Island - Irwandi; Yusuf, Ali Anwar (International Journal of Science and Society, 2023)
This article explores how inter-ethnic harmony in a multicultural society is formed, with a focus on the harmonization of ethnic Malays and Chinese on Belitung Island. This case study explores how interaction and integration occur between ethnic Malays and Chinese on Belitung Island so that harmonization is formed. This study uses a qualitative approach with data collection in the form of literature studies, observations and interviews with informants who come from ethnic Malays and Chinese. Social interaction between ethnic Malays and Chinese in Belitung has been running very harmoniously until now. Social interaction between the two ethnic groups is formed from an associative social process that arises from the principles of openness and equality. Social integration between ethnic Malays and Chinese in Belitung was formed from a relatively long process of social interaction with the principle of equality with the motto "Tong Ngin Fan, Ngin Jit Jong", which means that Chinese and Malays are the same or equal. In addition, social integration is also influenced by the high sense of tolerance between the two ethnic groups, so that social integration can be closely intertwined until now.